1998
DOI: 10.1007/s003300050483
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive vascular imaging of peripheral vessels

Abstract: The purpose of this review is to describe recent advances in non-invasive vascular imaging techniques and to discuss their current clinical applications for imaging of peripheral vessels. Principles for applying ultrasound, CT angiography (CTA), and magnetic resonance angiography (MRA) for non-invasive imaging of peripheral arteries and veins are presented. Clinical applications are reviewed for different vascular diseases, therapy planning, and follow-up studies. Conventional Doppler and color duplex sonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 77 publications
0
39
0
1
Order By: Relevance
“…However, since it is an invasive technique, TCA is generally now performed only as a pre- . e TCA lateral projection view revealed a complete occlusion of left planter artery and shows better the kinetics of blood flow as the distal part of the planter artery is supplied by the dorsalis pedis artery treatment procedure and is known to have some limitations and risks [2,3]. CT angiography is relatively non-invasive new technique introduced in the last 10 years for assessment of PAD [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since it is an invasive technique, TCA is generally now performed only as a pre- . e TCA lateral projection view revealed a complete occlusion of left planter artery and shows better the kinetics of blood flow as the distal part of the planter artery is supplied by the dorsalis pedis artery treatment procedure and is known to have some limitations and risks [2,3]. CT angiography is relatively non-invasive new technique introduced in the last 10 years for assessment of PAD [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is known to be invasive and has a definite morbidity [2,3]. Helical computed tomography (CT) scan has enormously improved during the last decade, with substantially shorter acquisition time and thinner slice sections enabling scanning of longer segment of the vascular tree with a single contrast-material injection.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular surgeons questioned found the MRA images equivalent in 75% of the cases, superior to the DSA results in 16% and inferior in 9% of the cases. Reimer and Landwehr [18] formulated the hypothesis that the MRA will replace the DSA in the near future due to its cost and time efficiency. The existing downsides of the MRA, for instance its flow dependence and the resulting artifacts, are considered solvable by Debatin and Hany [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already been published on the MRA as a means of evaluation for the vascular system of the lower extremity. In these publications, the comparability of the MRA and the DSA regarding the expressiveness of the vessel morphology could be assessed beyond any doubt [17][18][19][20]. We focused mainly on the issue of whether the MR angiography of the lower extremities for presurgical planning of reconstructive surgery is comparable or even superior to DSA or Duplex sonography as far as expressiveness, vascular anatomy and/or stenosis ratio of the vessels are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ability of SPIO to significantly reduce the spin-spin relaxation (T2) time is generally relied on for generating MR contrast, 68,99 it has also been demonstrated that SPIO can generate sufficient T1 contrast for biomedical applications as well; SPIO possess both high R1 and R2 relaxivities. 118,127 Upon removal of the magnetic field, Brownian motion is sufficient to randomize the SPIO orientations leaving no magnetic remanence. Brownian forces also prevent the aggregation of the SPIO due to magnetic attraction in solution.…”
Section: Magnetismmentioning
confidence: 99%